O conselho de direitos de crianças e adolescentes do município de João Pessoa-PB: desafios no exercício do controle social - Santana, Elaine Farias de (2017)
In the present work of master's thesis, the aim was to understand the exercise of social control, from the Municipal Council of the Child and Adolescent Rights - MCCAR, of the municipality of João Pessoa, Paraiba. In terms of theoretical perspective, the critical social theory of the Marxist tradition anchored the analysis. Social participation, social control and citizenship in the Brazilian context have been considered as the main analytical categories. It has a close relation with the social inequalities exacerbated by the capitalist societal order. The relationship between the State and civil society is based on legal bases that have developed and structured in line with the economic policy in force in each historical context. In this sense, we understand that instances of social control are adequate spaces to reflect on these issues. As a field of studies, the councils allow us to perceive the pressure power of social actors in guaranteeing rights consolidated in a legal framework, which in Brazil is the Federal Constitution of 1988. In the methodological procedures, we adopted qualitative field research with interview and the technique of content analysis. In terms of empirical research, advances in the expansion of rights councils have been identified. Challenges include gaps in the structure of boards, ongoing training in the conceptual, thematic and political aspects of the subjects involved in these spaces so that they can develop their attributions and competencies in the complex system that has been structured to account for this policy so peculiar. Another identified challenge is the need to build the planning of the activities of the council, as this issue has a direct impact on the followup, evaluation and necessary corrections in the policy for the care of children and adolescents. Without pretending to exhaust the discussions in this study, we infer that the rights councils of children and adolescents are usually spaces of resistance that, even in the face of the difficulties faced, have played a very important social role.